2017
DOI: 10.1371/journal.pone.0187717
|View full text |Cite
|
Sign up to set email alerts
|

Relief of endoplasmic reticulum stress enhances DNA damage repair and improves development of pre-implantation embryos

Abstract: Early-cleaving embryos are known to have better capacity to reach the blastocyst stage and produce better quality embryos compared to late-cleaving embryos. To investigate the significance of endoplasmic reticulum (ER) stress on early embryo cleavage kinetics and development, porcine embryos produced in vitro were separated into early- and late-cleaving groups and then cultured in the absence or presence of the ER stress inhibitor tauroursodeoxycholic acid (TUDCA). Developing embryos were collected at days 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…The fact that KDM5B and KDM5C attenuation also decreased development to blastocysts stage in non-UV exposed embryos may also be in consequence of accumulation of DSBs. This is supported by our previous findings revealing that late cleaving and less developmentally competent embryos have increased incidence of DSBs (Bohrer et al, 2015;Dicks et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The fact that KDM5B and KDM5C attenuation also decreased development to blastocysts stage in non-UV exposed embryos may also be in consequence of accumulation of DSBs. This is supported by our previous findings revealing that late cleaving and less developmentally competent embryos have increased incidence of DSBs (Bohrer et al, 2015;Dicks et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…After fertilization, a number of epigenetic changes are required to setup and modulate the embryo developmental program. Activation of transcriptional activity, cell lineage commitment and DNA damage repair are among the critical events regulated by epigenetic modifications in early developing embryos (Ostrup et al, 2013;Bohrer et al, 2015;Dahl et al, 2016;Dicks et al, 2017;Ding et al, 2017;Eckersley-Maslin et al, 2018;Rissi et al, 2019). Both maternal and paternal derived chromatins FIGURE 7 | Relative mRNA abundance of KDM5B and KDM5C in embryos exposed (UV+) or not (UV-) to UV radiation for 10 s at 36 h, Day 5 or Day 7 post-PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that tauroursodeoxycholic acid (TUDCA), an effective inhibitor of ER stress, can significantly relieve ER stress and block apoptosis [ 24 , 25 ]. Its beneficial effects on oocyte maturation in porcine [ 26 ] and preimplantation embryo development in both porcine [ 27 29 ] and bovine [ 30 ] are also recently confirmed by different laboratories. However, whether TUDCA-treatment might alleviate the ER stress of nuclear donor cells under serum starvation and hence increase the developmental potency of bovine SCNT embryos using these treated donors has not been studied or reported.…”
Section: Introductionmentioning
confidence: 84%
“…The function of cytoplasmic segregated p53 protein in SOD1G93A genotype neurons restrained the DNA repair process (Figure 2b) [39]. Generally, ER stress inhibits the DNA repair process and thus, increases DNA strand breaks [40,41]. Two ALS inducible RNA-binding proteins, TDP43 and FUS, participate in the DNA repair process [42].…”
Section: Sod1g93a Inhibits the Nucleic Localization Of Fals-related Rmentioning
confidence: 99%